2007
DOI: 10.4103/0019-5545.37320
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of severe mental illness in India: Against the simple industrialization hypothesis

Abstract: Background:Major international studies on course and outcome of schizophrenia suggest a better prognosis in the rural world and in low-income nations. Industrialization is thought to result in increased stigma for mental illness, which in turn is thought to worsen prognosis. The lack of an ethnographically derived and cross-culturally valid measure of stigma has hampered investigation. The present study deploys such a scale and examines stigmatizing attitudes towards the severely mentally ill among rural and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 12 publications
2
63
2
1
Order By: Relevance
“…26 These findings were contrary to an Indian study that proved more stigmatizing attitude towards persons with mental illness by the rural participants. 27 In support of earlier research, 28 present study also demonstrated, students those were familiar with people with mental illness hold least restrictive and more benevolent attitudes toward mental illness. Never the less, numerous studies among nursing 29 and medical students 30 revealed that there was a positive change in their attitudes towards persons with mental illness after completion of psychiatry course.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…26 These findings were contrary to an Indian study that proved more stigmatizing attitude towards persons with mental illness by the rural participants. 27 In support of earlier research, 28 present study also demonstrated, students those were familiar with people with mental illness hold least restrictive and more benevolent attitudes toward mental illness. Never the less, numerous studies among nursing 29 and medical students 30 revealed that there was a positive change in their attitudes towards persons with mental illness after completion of psychiatry course.…”
Section: Discussionsupporting
confidence: 86%
“…Ex: "It is not appropriate for a person with mental illness to get married"; (iv) Benevolence (reverse coded): includes eight items (18-23, 25, 26) related to kindness and sympathetic views of the respondents towards people with a mental illness. Ex: "People with mental illness can hold a job"; (v) Pessimistic prediction: composed of four items (27)(28)(29)(30) intended to measure the level of prejudice toward mental illness. Ex: "It is harder for those who have a mental illness to receive the same pay for the same job"; and (vi) Stigmatization: includes four items (31-34) that measure the discriminatory behavior of the students toward mental illness.…”
Section: Methodsmentioning
confidence: 99%
“…Negative attitudes and stigma directly affects the clinical practice in psychiatry (Byrne, 1999). Stigmatization of individuals with mental illnesses is widespread (Chowdhury et al, 2001;Jadav et al, 2007) and serves as a major barrier to proper mental health care and the better quality of life (Mann & Himelein, 2004;Charles et al, 2007). Reduction of stigma against persons with mental illness is a serious preventive work (Arboleda & Sartorius, 2008;Crisp et al, 2000) at all levels of mental health work-from clinic, hospitals, institution to community (Penn & Couture, 2002).…”
Section: Cross-cultural Communicationmentioning
confidence: 99%
“…In day to day practice it is seen that undergraduate nursing students show unfavorable attitudes toward psychiatric/mental health nursing as a career. 5 Nursing students are future health manpower of our country. They will be part of societal development.…”
Section: Introductionmentioning
confidence: 99%